Fitoremediacija s kovinami onesnaženih tal z uporabo sadik dreves - Al Sayegh-Petkovšek, Samar (Zbornik gozdarstva in lesarstva, 2010)
Phytoremediation was performed on two research plots at Poček military training ground. The first research plot (polluted with Pb and Cu) is situatedat the shooting range and the second in its close vicinity, where soil is less loaded with metals. Seedlings of five species (Alnus glutinosa L., Acer pseudoplatanus L., Betula pendula Roth., Pinus sylvestris L., Salix caprea L.) were planted on plots according to the standardised system; in addition, growth parameters and metal contents in roots, stems and shoots weremeasured as well. Although seedlings accumulate only Cd (BCF = 1.2) in their roots, and the rest of metals are taken up in smaller concentration and species specific, the majority of tree species have the potential for remediation and especially for phytostabilisation. Favourable ratio between bioaccumulation and translocation was determined for all species with the exception of Salix caprea, which was effective in taking up Cd in leaves (TF =6.9). The results of our study have shown that Pinus sylvestris is the most suitable species regarding growth parameters and metal uptake, whereas the least suitable is Salix caprea.
Keywords: drevje; fitoremediacija; onesnaženje; težke kovine